1999
DOI: 10.1136/bmj.319.7216.1031
|View full text |Cite
|
Sign up to set email alerts
|

Ecological analysis of ethnic differences in relation between tuberculosis and poverty

Abstract: Objective To examine the effect of ethnicity on the relation between tuberculosis and deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 17 publications
6
45
0
5
Order By: Relevance
“…In a recent study in Canada, Clark et al (2002)observed that tuberculosis incidence was higher in communities with a higher average housing density. Overcrowding housing conditions are known to increase exposure of susceptible people to those with infectious respiratory disease, and may increase the probability of transmission (Hawker et al, 1999;Tornee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Canada, Clark et al (2002)observed that tuberculosis incidence was higher in communities with a higher average housing density. Overcrowding housing conditions are known to increase exposure of susceptible people to those with infectious respiratory disease, and may increase the probability of transmission (Hawker et al, 1999;Tornee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Progression rates to active-TB (the infectious disease stage) are not uniform and show a strong correlation with the average community standard of living (Bloch et al 1989, Felton and Ford 1993, Mangtani et al 1995, Hawker et al 1999. Prior and throughout the nineteenth century, tuberculosis was one of the main causes of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…TB is no longer limited to under-developed nations and people from lower socioeconomic groups. This resurgence of TB could possibly be due to the increased migration and globalization, overcrowding and a corporate culture, immunosuppression especially in the form of human immunodeficiency virus (HIV) and hepatitis virus infection [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%